Common ash (Fraxinus excelsior L.) seeds as a new vegetable oil source. (September 2020) - Naderi, Mehran; Torbati, Mohammadali; Azadmard-Damirchi, Sodeif; Asnaashari, Solmaz; Savage, Geoffrey P.
Abstract: In this study, common ash ( Fraxinus excelsior L. ) seed oil compositions were determined for the first time. Effect of the moisture content and microwave pretreatment of the seeds on the oil yield and its composition were also investigated. The optimum level of moisture content to obtain the maximum oil (18.18%) yield was 1% with 3 min pre-treatment. The main triacylglycerol composition of the oil was linoleic–linoleic–oleic, followed by oleic-oleic-linoleic and linoleic–linoleic-linoleic. The main fatty acid of the oil was linoleic acid (C18:2), followed by oleic acid (C18:1) and palmitic acid (C16:0). The main phytosterol of the oil was β-sitosterol, followed by Δ 5 -avenasterol and campesterol. The main tocopherol of the oil was α-tocopherol, followed by β and γ-tocopherols. The main essential oil of the oil was bicyclogermacrene, followed by delta-cadinene. These results suggest that this oil is a good source of valuable nutritional compounds and that microwave pretreatment is a promising and environmentally friendly method to extract it as a new vegetable oil source. Highlights: Common ash ( Fraxinus excelsior L. ) seed oil compositions were determined. Moisture content and microwave pretreatment had significant effect on the oil yield. Ash seed oil (ASO) is a good source of valuable nutritional compounds. ASO was similar to other usual vegetable oils with high content of linoleic acid.